A proteção do consumidor-idoso em juízo e a prerrogativa de foro - Malfatti, Alexandre David (2007)
The "consumer's protection" wakes up a great interest in the society and in the organs of state power and it portrays the confluence of two movements on behalf of the citizens: the) the consumer's and b) the cash access to the Justice. Brazil should not flee to the world rule of the necessary protection of the consumer-senior. The Federal Constitution of 1.988 disposed expressly about the obligation of the State to defend the consumer (goods 5o, interruption XXXII and 170, V) and of the senior's protection for the family, for the society and for the State (art. 230). The actions of public politics of the Executive Power, of edition of norms for the Legislative Power, of judgments of the Judiciary Power and, finally, of the sphere toilet they cannot act against the consumer's legitimate interests. The law no. 8.078/90 (Code of Defense of the Consumer - CDC) and the Law n. 10.741/2003 (Statute of the Senior - EI) they took care of the regulation of the consumption relationship and of the senior, respectively. It is possible to establish a connection among those laws, in way to fasten parameters of the protection of the consumersenior. Several measures can facilitate the defense in judgment of the consumer-senior: the) creation of specialized judiciary organs, b) mechanisms that guarantee juridical attendance, c) inversion of the obligation of the proof and other internal providences of the process, d) forum prerogative. The prerogative of forum of the consumersenior appears, then, as fundamental instrument for the cash access to the Justice. It is forecast of CDC and of EI that should be applied in benefit of him consumer-senior, so much in the individual actions, as in the collective actions. The interpretation of the competence norms should be made in harmony with that prerogative, always in way to an useful result for the protection of the consumer-senior